2021
DOI: 10.3390/polym13244410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Washing Time and Washing Solution on the Biocompatibility and Mechanical Properties of 3D Printed Dental Resin Materials

Abstract: Three-dimensional (3D) printing technology is highly regarded in the field of dentistry. Three-dimensional printed resin restorations must undergo a washing process to remove residual resin on the surface after they have been manufactured. However, the effect of the use of different washing solutions and washing times on the biocompatibility of the resulting resin restorations is unclear. Therefore, we prepared 3D-printed denture teeth and crown and bridge resin, and then washed them with two washing solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 59 publications
(72 reference statements)
2
35
0
1
Order By: Relevance
“…Post-processing methods involving prolonged soaking in organic solvents (e.g., isopropanol, methanol) allow the unpolymerized monomers in the inner layers of the structure to be reached and washed out. Previous studies have shown a positive correlation between cell viability and scaffold washing time ( Grigaleviciute et al, 2020 ; Hwangbo et al, 2021 ). In addition, washing of the specimens in an ultrasonic bath was shown to improve cell proliferation significantly ( González et al, 2020 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Post-processing methods involving prolonged soaking in organic solvents (e.g., isopropanol, methanol) allow the unpolymerized monomers in the inner layers of the structure to be reached and washed out. Previous studies have shown a positive correlation between cell viability and scaffold washing time ( Grigaleviciute et al, 2020 ; Hwangbo et al, 2021 ). In addition, washing of the specimens in an ultrasonic bath was shown to improve cell proliferation significantly ( González et al, 2020 ).…”
Section: Discussionmentioning
confidence: 94%
“…Among the techniques proposed for the fabrication of scaffolds, precise control of the scaffold structure can be provided by photopolymerization methods such as Laser Driect Writing (LDW) ( Danilevicius et al, 2012 ; Weisgrab et al, 2020 ; Sharaf et al, 2022 ), Stereolithography/Direct Light Processing (SLA/DLP) ( González et al, 2020 ; Hart et al, 2020 ; Ao-Ieong et al, 2021 ; Bayarsaikhan et al, 2021 ; 2022 ; Hwangbo et al, 2021 ), holographic lithography ( Stankevicius et al, 2012 ) and others. SLA and DLP are the two most widely used technologies in commercial UV desktop printers.…”
Section: Introductionmentioning
confidence: 99%
“…The resin has a density of 1.10 g/ cm 3 and a tensile modulus of elasticity of 1.05 GPa [45] which is suitable for general modeling and industrial prototype proofing. Next, the printed samples were cleaned using ethyl alcohol at 70% concentration with a washing time of 3 min [46,47]. The structures were built with external supports with cylindrical shape and conical connection that were removed manually by pliers.…”
Section: Model Fabricationmentioning
confidence: 99%
“…[11] The biocompatibility of the resource material in biomedical devices could be dependent on the amount of the active components, physical properties, and the duration of the study. [31,32] The toxicological assessment of the biomedical products including 3D-printed cardiovascular stents could provide critical insights into post-treatment strategies to minimize the material-related adverse effects and reduce the associated risks in patients during their clinical application, [33] subsequently facilitating the regulatory preapproval process. [34] An assessment of therapeutic efficacy and biocompatibility of nanomaterial-based materials including hydrogels seems to be integral for the successful development of biomedical devices, especially for cardiovascular application including devices against atherosclerosis, [20] tissue/muscle regeneration in myocardia infection, [35] and activation of cardiac fibroblasts that is a pathological, phenotypic transition in cardiac fibrosis.…”
Section: Introductionmentioning
confidence: 99%